Language Center Design and Management in the Post-Language Laboratory Era - Kronenberg, Felix A. (IALLT Journal of Language Learning Technologies, 2014)
This article is based on a survey sent to the IALLT membership and to members of all regional groups. Divided into 3 sections titled “Personal,” “Profession/Organization” and “Language Center,” the survey aims to provide an understanding of current trends and issues in the field of language learning and technology, language center design, and language center management. Findings from the survey reveal a diverse field that differs greatly from institution to institution, one that is trying to adapt to disruptive technological and pedagogical changes and to balance relatively stable physical spaces and structures with rapidly changing and unstable technological and educational environments.